OBESITY IS ASSOCIATED WITH LACK OF ACCESS TO DENTAL CARE AND PHYSICAL ACTIVITY AMONG OLDER ADULTS: A CROSS-SECTIONAL STUDY - Natália Rigon Scalco; Francisco Wilker Mustafa Gomes Muniz; Nathália Prigol Rosalen; Diandra Genoveva Sachetti; Nathalia Ribeiro Jorge da Silva; Paulo Roberto Grafitti Colussi (Brazilian Society of Geriatrics and Gerontology, 2021)
OBJECTIVE: This study evaluated the prevalence of obesity and associated factors among older adults. METHODS: This was a household-based cross-sectional study involving 282 individuals aged ≥ 60 years recruited in the city of Veranópolis, Brazil, using random probabilistic sampling. Participants underwent a clinical oral examination and completed a structured questionnaire. Obesity was determined based on body mass index (BMI). Individuals were divided into two groups based on the presence (BMI ≥ 30 kg/m2) or absence of obesity (BMI < 30 kg/m2). Uni- and multivariate analyses were performed using Poisson regression with robust variance. RESULTS: The prevalence of obesity was 34% (n = 96). Each 1-year increase in age resulted in a 3.09% decrease in the likelihood of being classified as having obesity (prevalence ratio [PR] = 0.969; 95% confidence interval [95%CI] 0.949 - 0.989). Older adults that reported walking < 5 or ≥ 5 times per week were 39.65 and 37.20% less likely to be classified as obese. The PRs of obesity in former and non-smokers were 4.40 and 5 times higher, respectively, than in current smokers (p < 0.05). Older adults with no access to dental care were 51.72% (p = 0.013) more likely to present with obesity. CONCLUSIONS: There was a high prevalence of obesity among older adults. Obesity was associated with lower age, smoking status, no access to dental care, and a lack of physical activity.